MOESM2 of Estimation of breeding values for uniformity of growth in Atlantic salmon (Salmo salar) using pedigree relationships or single-step genomic evaluation - Panya Sae-Lim; Kause, Antti; Lillehammer, Marie; Mulder, Han (Figshare, 2017)
Additional file 2: Table S1. Cross-validation based on sire-dam DHGLM. The data provided represent the results from 10-fold cross-validations based on sire-dam DHGLM.